Endogenous Glucocorticoid Response to Single-Dose Dexamethasone for Croup in Children: A Pharmacodynamic Study. Issue 1 (January 2020) - Gill, Natasha; Sirizzotti, Natalie; Johnson, David; Joubert, Gary; Kucey, Andrew S.; Tieu, Alvin; Urquhart, Brad L.; Columbus, Melanie; Lim, Rodrick; Rieder, Michael; Mehrotra, Shruti; Hartjes, Emily D.; et al.
Abstract : Objectives: Dexamethasone is associated with adrenal insufficiency in adults and children with chronic disease. This association has not been studied after single-dose oral dexamethasone, the standard of care for children with croup. We hypothesized that single-dose oral dexamethasone in children with croup is associated with a transient decrease in endogenous glucocorticoids. Methods: We conducted a prospective, 2-arm, pharmacodynamic study of single-dose oral dexamethasone 0.6 mg/kg (maximum, 12 mg) in children older than 2 years with croup compared with controls (children with febrile upper respiratory tract infections who did not receive dexamethasone). Primary outcome was urinary 6β-hydroxycortisol–cortisol ratio. Results: Twenty-seven children were analyzed (22 with croup and 5 with upper respiratory tract infections). Median 6β-hydroxycortisol–cortisol ratios before dexamethasone, the following morning, and on days 1, 3, and 7 were 2.8, 2.2, 2.0, 2.8, and 2.6, respectively. Among controls, the median 6β-hydroxycortisol–cortisol ratios at the same time intervals was 1.9, 1.5, 1.8, 2.5, and 1.7, respectively. There were no significant differences in the change from time 0 between groups at any time point. There were no serious adverse events or infectious complications. Conclusions: Single-dose oral dexamethasone is not associated with decreased endogenous corticosteroid levels in children with croup. Future studies should use criterion standard tests to rule out suppression of the hypothalamic-pituitary-adrenal axis and be powered sufficiently to identify adverse clinical outcomes.